2021
DOI: 10.1016/j.isci.2021.102828
|View full text |Cite
|
Sign up to set email alerts
|

Biophotoelectrochemistry for renewable energy and environmental applications

Abstract: Biophotoelectrochemistry (BPEC) is an interdisciplinary research field and combines bioelectrochemistry and photoelectrochemistry through the utilization of the catalytic abilities of biomachineries and light harvesters to accomplish the production of energy or chemicals driven by solar energy. The BPEC process may act as a new approach for sustainable green chemistry and waste minimization. This review provides the state-of-the-art introduction of BPEC basics and systems, with a focus on light harvesters and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 157 publications
(191 reference statements)
1
15
0
Order By: Relevance
“…57 This was consistent with the results reported by previous studies, 58,60 in which an Fpo-dependent electron transfer pathway was demonstrated to effectively support the CO 2 -to-CH 4 conversion by M. barkeri in the absence of hydrogenases. As expected, the bifunctional CODH/acetylcoenzyme A synthase (CODH/ACS) that contained distinct, spatially separated active sites for CODH and ACS activity (connected by a hydrophobic tunnel) 61,62 was highly expressed in the BPEC-CO system, particularly under the higher CO concentration and light irradiation. The abundant CODH/ ACS enzyme complex could catalyze the oxidation of CO to CO 2 with Fd ox as an electron acceptor, resulting in a high cellular Fd red :Fd ox ratio for methanogenesis, and enhance the acetyl-CoA synthesis for further biomass production.…”
Section: ■ Materials and Methodssupporting
confidence: 65%
“…57 This was consistent with the results reported by previous studies, 58,60 in which an Fpo-dependent electron transfer pathway was demonstrated to effectively support the CO 2 -to-CH 4 conversion by M. barkeri in the absence of hydrogenases. As expected, the bifunctional CODH/acetylcoenzyme A synthase (CODH/ACS) that contained distinct, spatially separated active sites for CODH and ACS activity (connected by a hydrophobic tunnel) 61,62 was highly expressed in the BPEC-CO system, particularly under the higher CO concentration and light irradiation. The abundant CODH/ ACS enzyme complex could catalyze the oxidation of CO to CO 2 with Fd ox as an electron acceptor, resulting in a high cellular Fd red :Fd ox ratio for methanogenesis, and enhance the acetyl-CoA synthesis for further biomass production.…”
Section: ■ Materials and Methodssupporting
confidence: 65%
“…These results were consistent with the periodic CH 4 production data. It is likely that the metal photocatalysts, being prone to photocorrosion, released heavy metals and poisoned the cells during the long-term photoreaction ( Sakimoto et al, 2018 ; Ye et al, 2021 ). Moreover, metals such as Cd can inhibit the electron transport chain and induce the production of reactive oxygen species (ROS), thereby causing oxidative damage to the cells ( Wang et al, 2004 ).…”
Section: Resultsmentioning
confidence: 99%
“…As the methanogenesis efficiency was greatly limited by the rapid reorganization of CdS photogenerated charges, nickel-doped cadmium sulfide ( Ni@CdS ) was used to improve the electron–hole separation efficiency to enhance their methanogenesis performance ( Ye et al, 2020 ). Although the introduction of Ni can overcome the issue caused by CdS photogenerated electron separation, the metal photocatalyst itself is prone to photocorrosion, heavy metal release, and microbial poisoning, which are still key problems that result in the instability and non-cyclability of BAHs ( Ye et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The semiartificial photosynthesis, which integrates an artificial photosensitizer with a biocatalyst, shows great potential in converting solar energy into specific chemicals. Typically, upon irradiation, photoexcited electrons from the photosensitizer are used by a nonphototrophic microorganism to produce the target metabolites . The systems have been demonstrated to produce diverse chemicals, such as hydrogen, acetate, and methane, and remove pollutants or recover high-energy chemicals from wastewater. For example, a cadmium sulfide-photosensitized Thiobacillus denitrificans (CdS/T.…”
Section: Introductionmentioning
confidence: 99%
“…denitrificans) is capable of removing nitrate (NO 3 – ) and recovering high purity of nitrous oxide (N 2 O) from NO 3 – -polluted wastewater driven by light . In addition to NO 3 – removal, the semiartificial photosynthesis system is demonstrated to detoxify heavy metal ions (e.g., Cr 6+ , Se 4+ , and As 3+ ), along with the conversion of inorganic carbon to chemicals for wastewater . Due to the excellent performance in solar energy conversion and environmental application, explosive research on the semiartificial photosynthesis systems has been triggered in recent years.…”
Section: Introductionmentioning
confidence: 99%